1992
DOI: 10.1029/91jb02572
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the reflectivity of the moho transition zone beneath the Midcontinent Rift System of North America: Results from true amplitude analysis of GLIMPCE data

Abstract: True amplitude processing of The Great Lakes International Multidisciplinary Program on Crustal Evolution seismic reflection data from the Midcontinent Rift System of North America shows large differences in the reflectivity of the Moho transition zone beneath the axial rift, beneath the rift flanks, and outside of the rift. The Moho reflection from the axial rift has a discontinuous, diffractive character marginally stronger (several decibels) than an otherwise transparent lower crust and upper mantle. Beneat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…This program involved multichannel seismic reflection studies in the Great Lakes (e.g., Behrendt et al 1988;Green et al 1989;Cannon et al 1989;Hutchinson et al 1992), wide-angle seismic reflection and refraction recordings from air-gun sources (Epili and Mereu 1989;Tr6hu et al 1991), and aeromagnetic surveying (Teskey et al 1991). The reflection profiles show that the rift basins are asymmetric and filled with up to 30 km of rift-related volcanic and sedimentary rocks (Behrendt et al 1988;Green et al 1989).…”
Section: Midcontinent Riftmentioning
confidence: 97%
See 2 more Smart Citations
“…This program involved multichannel seismic reflection studies in the Great Lakes (e.g., Behrendt et al 1988;Green et al 1989;Cannon et al 1989;Hutchinson et al 1992), wide-angle seismic reflection and refraction recordings from air-gun sources (Epili and Mereu 1989;Tr6hu et al 1991), and aeromagnetic surveying (Teskey et al 1991). The reflection profiles show that the rift basins are asymmetric and filled with up to 30 km of rift-related volcanic and sedimentary rocks (Behrendt et al 1988;Green et al 1989).…”
Section: Midcontinent Riftmentioning
confidence: 97%
“…T h i s study found thickened crust and highly disrupted Moho under the rift axis compared with the rift flanks (Epili and Mereu 1989). Hutchinson et al (1992) reprocessed several GLIMPCE reflection lines using relative true amplitude processing techniques. They found well-developed Moho reflectivity under the rift flanks, with two identifiable boundaries.…”
Section: Midcontinent Riftmentioning
confidence: 98%
See 1 more Smart Citation
“…For the MCR, the combination of seismic and gravity anomalies of Lake Superior has been interpreted as underplating in the lower crust up to 15 km thick (Behrendt et al., 1990; Hamilton & Mereu, 1993; Hinze et al., 1992; Hutchinson et al., 1990, 1992; Shay & Tréhu, 1993; Zhang et al., 2016). Behrendt et al.…”
Section: Discussionmentioning
confidence: 99%
“…(1990) and Hutchinson et al. (1992) proposed that the high‐velocity material that makes up the present‐day lower crust was probably originally mantle material that now appears to have crustal properties because of the large volume of intruded gabbroic rocks. Although there are often multiple seismic reflectors within the underplated layer, its upper and lower boundaries usually display distinct seismic reflectors that are seen as both normal‐incidence and wide‐angle reflections (Thybo & Artemieva, 2013).…”
Section: Discussionmentioning
confidence: 99%